2012
DOI: 10.1186/1755-8794-5-32
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in glutamate cysteine ligase catalytic subunit (GCLC) is associated with sulfamethoxazole-induced hypersensitivity in HIV/AIDS patients

Abstract: BackgroundSulfamethoxazole (SMX) is a commonly used antibiotic for prevention of infectious diseases associated with HIV/AIDS and immune-compromised states. SMX-induced hypersensitivity is an idiosyncratic cutaneous drug reaction with genetic components. Here, we tested association of candidate genes involved in SMX bioactivation and antioxidant defense with SMX-induced hypersensitivity.ResultsSeventy seven single nucleotide polymorphisms (SNPs) from 14 candidate genes were genotyped and assessed for associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 48 publications
1
37
0
1
Order By: Relevance
“…Синтез глутатиона происходит под воздействием фермента глутаматцистеинлигазы (GCL), состоящей из двух субъединиц -регуляторной субъединицы (GCLM) и обеспечивающей каталитическую актив-ность фермента (GCLC) [19]. В настоящем исследовании мы провели изуче-ние полиморфизма С129Т (rs 17883901) гена GCLC, при котором происходит замена цитозина на тимин в позиции 129.…”
Section: результаты и обсуждениеunclassified
“…Синтез глутатиона происходит под воздействием фермента глутаматцистеинлигазы (GCL), состоящей из двух субъединиц -регуляторной субъединицы (GCLM) и обеспечивающей каталитическую актив-ность фермента (GCLC) [19]. В настоящем исследовании мы провели изуче-ние полиморфизма С129Т (rs 17883901) гена GCLC, при котором происходит замена цитозина на тимин в позиции 129.…”
Section: результаты и обсуждениеunclassified
“…A study of 14 candidate genes in HIV-infected patients with SMX hypersensitivity (102 cases vs 318 controls) also found significant association with SNP rs76114 2T>G in GCLC (adjusted p = 0.045) [73]. Heterozygous (TG) and homozygous (GG) are at increased risk compared with TT genotype (OR: 2.2 and 3.3, respectively).…”
Section: Antibacterial Agentsmentioning
confidence: 99%
“…Polymorphismresulted GCL enzyme expression and activity are significantly reduced. Moreover, phenotype indicates the severity of the disease, such as myocardial infarction, cancer, diabetes and HIV / AIDS (Koide et al, 2003;Wang et al, 2012). The GCL gene polymorphism and the level of glutathione and F2-isoprostanes in the TB patients and normal individuals have been describe (Nwanjo and Oze, 2007;Yuniastuti et al, 2013), but for the contacts of person with infectious TB have never been reported.…”
Section: Introductionmentioning
confidence: 99%